Filsafat Terapan Pendidikan Tinggi Keagamaan Islam Akomodatif Bagi Penyandang Disabilitas - Soleh, Akhmad; Said, Nur (LP2M IAIN kUDUS, 2021)
At the end of 2021, the President of the Republic of Indonesia has signed the formation of the National Commission for Disabilities (KND). They certainly need research data to support research-based policies. This article formulates the applied philosophy of disability-responsive Islamic higher education in Indonesia with a case study at IAIN Alaudin Makassar. This study uses a philosophical, phenomenological and educational policy approach. The data collected by observation, interviews and documentation were then analyzed with a philosophical and phenomenological perspective within the framework of education policy. This study concludes that the most important thing and is the main capital in building an inclusive campus is the issue of world view, namely the philosophical foundation that gives birth to the attitudes, behavior and culture of the campus community and society as a whole to build an inclusive campus for students with disabilities. With a philosophical vision of becoming a center for enlightenment and transformation of science and technology based on Islamic civilization, this is a curriculum idea that has the potential to be reconstructed into a curriculum document as a reference in curriculum implementation in achieving disability-responsive educational goals. This framework of thinking is part of an applied Islamic paradigm that is in line with the reasoning of the religion of peace or as a form of prophetic thinking paradigm based on theo-anthropocentric existentialist philosophy of Islamic Religious Higher Education in Indonesia